Self-healing Performance of Vulcanized Natural Rubber using MgO/ZnO as a Binary Activator - Nghiem, Thi Thuong; Le, Minh Tho; Dang, Viet Hung; Phan, Trung Nghia; Pham, Van Hai; Nguyen, Ba Lam; Kawahara, Seiichi (JST: Engineering And Technology For Sustainable Development, 2025)
Self-healing vulcanized natural rubber (S-H V-NR) was prepared with MgO/ZnO as a binary activator system in this study. Standard Vietnam Rubber graded 3L (SVR3L) was used as NR source. The SVR3L was vulcanized with different activators of ZnO, MgO/ZnO, or MgO and other vulcanizing reagents. The total amount of activators were 5 parts per hundred rubber (phr); in which the MgO/ZnO binary activator system was compounded with the SVR3L at a 3:2 ratio of MgO to ZnO amount. Furthermore, sulfur amount was either 1.0 or 1.5 phr. V-NR underwent S-H process at S-H temperatures of 25, 50, or 100 °C for S-H times of either 12 or 24 h. The cure characteristics of the NR compounds were measured to examine optimal vulcanization time (t90) and maximum torque (MH). Raman spectroscopy was used to evaluate relative ratio of disulfide and polysulfide bonds. Self-healability was assessed by determining the stress and strain at break of S-H V-NR before and after S-H process. The results showed that the use of the MgO/ZnO as binary activator system and MgO as activator to replace ZnO shortened the t90. V-NR prepared with MgO activator had the best self-healability among all V-NR since the disulfide bonds were dominantly formed over polysulfide bonds when the MgO activator was used, based on the results of Raman measurements for V-NR. Meanwhile, the self-healability of V-NR prepared with the MgO activator at high temperature did not depend on the S-H time.